Effects of N-methyl-thiotetrazole cephalosporin on haemostasis in patients with reduced serum vitamin K1 concentrations. Issue 11 (November 1986) - Mackie, I J; Walshe, K; Cohen, H; McCarthy, P; Shearer, M; Scott, S D; Karran, S J; Machin, S J
Abstract : Two patients with low random serum vitamin K1 concentrations but with normal prothrombin times and normal biological assays of the vitamin K dependent coagulation proteins were treated with an N-methyl-thiotetrazole cephalosporin (cefotetan) postoperatively. Four to six days later both patients developed a prolonged prothrombin time and a noticeable and specific lowering of the clotting activities of factors II, VII, IX and X, though the serum vitamin K1 concentrations remained unchanged. Crossed immunoelectrophoresis of prothrombin showed the appearance of a second peak corresponding to descarboxyprothrombin (PIVKA II). These abnormalities corrected after vitamin K administration. These data are consistent with the hypothesis that cephalosporins with an N-methyl-thiotetrazole side chain inhibit the hepatic utilisation of vitamin K but that this only causes hypoprothrombinaemia when liver reserves of vitamin K are low.